ANALYSIS OF THE EFFECT OF FOREIGN INVESTMENT AND PROVINCIAL MINIMUM WAGE ON GROSS REGIONAL DOMESTIC PRODUCT (CASE STUDY OF 8 PROVINCES IN INDONESIA) - Wahyudi Nuryanto Dwi Putra; Mochamad Ridwan (Journal of Research in Social Science and Humanities, 2025)
This study aims to provide an analysis of the effect of Foreign Direct Investment (FDI) and Provincial Minimum Wage (UMP) on Gross Regional Domestic Product (GRDP) in eight provinces in Indonesia, taking into account the dynamics and complexity of the economy in 8 provinces, including DKI Jakarta, East Java, West Java, Central Java, Banten, North Sumatra, South Sumatra, and South Sulawesi in the period 2018 to 2023. This study uses a REM model based on 2 tests including chow and hausman tests. The results indicate that FDI contributes significantly to the rate of GRDP in eight provinces in Indonesia, including South Sumatra, North Sumatra, DKI Jakarta, West Java, Central Java, East Java, Banten, and South Sulawesi during the period 2018 to 2023. The increase in the value of FDI is in line with the increase in GRDP in these provinces. In addition, UMP also influenced GRDP in eight provinces in Indonesia during the period 2018 to 2023. An increase in UMP is positively correlated with GRDP in eight provinces in Indonesia.